Organization of school work in focus: the limits of antidemocratic inheritance and potential of participatory processes - Maria Vieira Silva (Universidade Estadual Paulista Júlio de Mesquita Filho, 2011)
Historically, democratic and participatory processes in the Brazilian society, and specifically in school, have been permeated by intermittences, weaknesses and resistances caused by multiple determinations. The text focuses on aspects concerningthe organization of education work through two lines of analysis: the first angle refers to the social constructs of structural and organic nature linked to relations of power andanti-democratic practices of the society in general. The second angle reference to a kindof ethnographic research, conducted within a public school in the Minas Gerais state. We seek to grasp the challenges on building practices and strategies in support of the participatory processes of the school community in the pedagogic project design and in the operation of the school board. We propose, with these analyses, to contribute withreflections on the status of teachers, as a subject, in the school organization throughconnections with work activities related to their everyday practice.